Faktor-Faktor Yang Mempengaruhi Manajemen Persediaan: Sistem Informasi Akuntansi Dalam Siklus Pendapatan, Siklus Pengeluaran Dan Siklus Sumber Daya Manusia - Syafina Amira Putri; Cris Kuntadi; Rachmat Pramukty (Universitas Katolik Widya Karya Malang, 2023)
In a research or scientific article, previous research or relevant research is very important. Leading research or relevant research is useful for strengthening theories and phenomena of the relationship or influence between variables. This article reviews the factors that influence inventory management, namely accounting information systems in the revenue cycle, expenditure cycle, and human resource cycle, a literature study on Accounting Information Systems. The purpose of this article is to develop a hypothesis of influence between variables that can be used in further research. The results of this literature review article are: 1) The accounting information system in the revenue cycle influences preparation management; 2) The accounting information system in the expenditure cycle affects inventory management; and 3) The accounting information system in the human resource cycle influences the preparatory management.